Badania nad rachunkiem kosztów w Polsce na podstawie "Zeszytów Teoretycznych Rachunkowości" Stowarzyszenia Księgowych w Polsce - Rubik, Jolanta (Research on Costing in Poland Based on Accounting Theoretical Journals Published by Accountants Association in Poland, 2005)
Accounting Theoretical Journals can be treated as a representative sample of Polish accountants and academics interests. They are also a professional forum for presentation of research results, experiences and scientists' opinions. The paper is a statistic review of scientific research results which are included and presented in the Accounting Theoretical Journals.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1079, s. 293-299